Successful factors for knowledge management system implementation: case study of sistem pengurusan maklumat Bersepadu1 NAHRIM / Mohd Amin Othman - Othman, Mohd Amin (2013)
This study attempted to identify the successful factors for Knowledge Management System in NAHRIM for the implementation of Sistem Pengurusan Bersepadu1 NAHRIM (SPMB1N). The overall work of this study will be based on the current KM Simplemented in NAHRIM, which is National Hydraulics Data Repository (GEDUNG).This paper discussed on the success factor of KMS implementation in other organization. Target focus group for this study is the personnel who contributed directly to the application namely desk officer and support staff as well as researcher and top management. Survey and interview was chosen as a medium to gain input for this study from target focus group. The main idea behind this research was to examine the key factor that can influence the successful usage as well as implementation of SPMB1N.Due to some unknown factor, the usage of the current application was not as expected. This study revealed the factor behind the underutilization. Acceptance levels of the current application were presented as well as successful factor captured from the analysis for the successful implementation of SPMB1N. This study find and discussed several factor such as top management support, reward system and training are among the list of recommendation that NAHRIM can use to ensure the successful implementation of SPMB1N.